2022
DOI: 10.3390/ijms23031899
|View full text |Cite
|
Sign up to set email alerts
|

Proglumide Reverses Nonalcoholic Steatohepatitis by Interaction with the Farnesoid X Receptor and Altering the Microbiome

Abstract: Nonalcoholic steatohepatitis (NASH) is associated with obesity, metabolic syndrome, and dysbiosis of the gut microbiome. Cholecystokinin (CCK) is released by saturated fats and plays an important role in bile acid secretion. CCK receptors are expressed on cholangiocytes, and CCK-B receptor expression increases in the livers of mice with NASH. The farnesoid X receptor (FXR) is involved in bile acid transport and is a target for novel therapeutics for NASH. The aim of this study was to examine the role of proglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…Proglumide is the only CCK receptor antagonist that increases bile flow 21 and decreases bile acid concentration in animal models; therefore, we studied the interaction of proglumide with FXR using a human luciferase reporter assay and demonstrated that proglumide interacted with FXR as a partial agonist. 42 Since bile acids are affected by the gut microbiome, chronic proglumide therapy in mice also altered the microbiome, rendering it less hepatotoxic and increasing beneficial bacteria species. 42 These reasons are some of the myriad potential mechanisms through which proglumide may interact to decrease NASH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proglumide is the only CCK receptor antagonist that increases bile flow 21 and decreases bile acid concentration in animal models; therefore, we studied the interaction of proglumide with FXR using a human luciferase reporter assay and demonstrated that proglumide interacted with FXR as a partial agonist. 42 Since bile acids are affected by the gut microbiome, chronic proglumide therapy in mice also altered the microbiome, rendering it less hepatotoxic and increasing beneficial bacteria species. 42 These reasons are some of the myriad potential mechanisms through which proglumide may interact to decrease NASH.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Since bile acids are affected by the gut microbiome, chronic proglumide therapy in mice also altered the microbiome, rendering it less hepatotoxic and increasing beneficial bacteria species. 42 These reasons are some of the myriad potential mechanisms through which proglumide may interact to decrease NASH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholangiocytes are a heterogenous population of epithelial cells that line bile ducts. Cholangiocytes can be activated to participate in hepatic inflammation and regulate liver fibrosis by interacting with myofibroblasts [111]. For example, cholecystokinin (CCK) released by duodenal enteroendocrine I-cells in response to dietary lipids and proteins can activate CCK receptors on cholangiocytes to promote NASH progression.…”
Section: Ductular Reaction and Biliary Epithelial Cell Injurymentioning
confidence: 99%
“…Numerous FXR agonists that have been developed for the treatment of NAFLD are in preclinical and clinical trials at present. The most advanced FXR agonist in clinical development is obeticholic acid [ 6 , 7 ], which was approved by the US Food and Drug Administration (FDA) for the treatment primary biliary cholangitis (PBC) in 2016, and which is currently being investigated in clinical evaluation for the treatment of NAFLD. Obeticholic acid improves a variety of metabolic characteristics, such as liver steatosis, liver inflammation, and fibrosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%